2011
DOI: 10.1016/j.jare.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Fatal acute myocarditis and fulminant hepatic failure in an infant with pandemic human influenza A, H1N1 (2009) virus infection

Abstract: We report the clinical presentation of a 10 month-old infant who succumbed with acute myocarditis and fulminant hepatic failure associated with a virologically confirmed human influenza A, H1N1 (2009) virus infection. To date, this is the first pediatric patient presenting with this fatal combination of complications during the current H1N1 pandemic. Therefore, we recommend meticulous assessment and follow up of the cardiac status, liver enzymes and coagulation profile in all pediatric patients with severe H1N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Carrillo-Esper et al, in 2010, reported two adult H1N1 patients with hepatic involvement 1. El-Shabrawi et al, in 2011, reported a 10-month-old child with acute myocarditis and fulminant hepatic failure associated with H1N1 6. The subject of the current case report had acute hepatic failure that presented as jaundice, elevated liver enzymes, and coagulopathy.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Carrillo-Esper et al, in 2010, reported two adult H1N1 patients with hepatic involvement 1. El-Shabrawi et al, in 2011, reported a 10-month-old child with acute myocarditis and fulminant hepatic failure associated with H1N1 6. The subject of the current case report had acute hepatic failure that presented as jaundice, elevated liver enzymes, and coagulopathy.…”
Section: Discussionmentioning
confidence: 64%
“… 1 El-Shabrawi et al, in 2011, reported a 10-month-old child with acute myocarditis and fulminant hepatic failure associated with H1N1. 6 The subject of the current case report had acute hepatic failure that presented as jaundice, elevated liver enzymes, and coagulopathy. Most of the other causes of liver failure had been ruled out by relevant investigations.…”
Section: Discussionmentioning
confidence: 88%
“…Extrapulmonary involvement is extremely rare for influenza viruses, which may present as severe gastrointestinal complications, such as pancreatitis, hemorrhagic gastritis, and Reye’s syndrome, and influenza-associated myocarditis and pericarditis. 35…”
Section: Discussionmentioning
confidence: 99%
“…Extrapulmonary involvement is extremely rare for influenza viruses, which may present as severe gastrointestinal complications, such as pancreatitis, hemorrhagic gastritis, and Reye's syndrome, and influenza-associated myocarditis and pericarditis. [3][4][5] Influenza A H3N2 is associated with increased mortality in pediatric patients with underlying diseases, age less than 5 years (especially <6 months), and coinfections with Staphylococcus aureus or Streptococcus pneumonia. 6 Even though underlying diseases have been implicated as a cause of increased mortality, 40% of influenza-related deaths in children have been shown to have no association with such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…El-Shabrawi et al8 published a case of acute myocarditis and fulminant hepatic failure in an infant with pandemic human influenza A, H1N1 in a 10-month-old child; while Sánchez-Torrent et al9 described a 3-month-old infant with H1N1 encephalitis.…”
Section: Discussionmentioning
confidence: 99%